Reflecting on Use of the GRADE Process for Development of the 2013 PAD Guidelines - Davidson, Judy E.; Tung, Avery; Kishman, Charles P., Jr.; Barr, Juliana (Seminars in Respiratory and Critical Care Medicine, 2013)
This article evaluates the methodology used to develop the updated American College of Critical Care Medicine/Society of Critical Care Medicine Pain Agitation and Delirium (PAD) Guidelines in terms of (1) evaluating the role of a medical librarian in the guidelines development process; (2) summarizing the impressions of the guideline task force members on the use of Grades of Recommendation, Assessment, Development, and Evaluation and anonymous voting to develop guideline questions, statements, and recommendations; and (3) analyzing the impact of this approach to developing clinical practice guidelines on interrater reliability in evaluating evidence, statements, and recommendations.
Keywords: evidence-based medicine; evidence-based nursing; critical care; outcome assessment; technology assessment